2020
DOI: 10.1038/s41598-020-73412-6
|View full text |Cite
|
Sign up to set email alerts
|

Acute cardiovascular health effects in a panel study of personal exposure to traffic-related air pollutants and noise in Toronto, Canada

Abstract: Urban populations are often simultaneously exposed to air pollution and environmental noise, which are independently associated with cardiovascular disease. Few studies have examined acute physiologic responses to both air and noise pollution using personal exposure measures. We conducted a repeated measures panel study of air pollution and noise in 46 non-smoking adults in Toronto, Canada. Data were analyzed using linear mixed-effects models and weighted cumulative exposure modeling of recent exposure. We exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 69 publications
2
11
0
1
Order By: Relevance
“…The study found that BC mediated most of the cardiovascular health damage, followed by noise. The effects of BC and noise on cardiac autonomic nerve function have also been demonstrated in other studies (5)(6)(7). BC is mainly emitted by traffic transport, where a high level of noise is usually produced simultaneously.…”
Section: Discussionsupporting
confidence: 55%
“…The study found that BC mediated most of the cardiovascular health damage, followed by noise. The effects of BC and noise on cardiac autonomic nerve function have also been demonstrated in other studies (5)(6)(7). BC is mainly emitted by traffic transport, where a high level of noise is usually produced simultaneously.…”
Section: Discussionsupporting
confidence: 55%
“…In Indian megacities like Delhi, the increased number of vehicles, resuspension of dust particles, construction activities, biomass burning, and other unregulated anthropogenic activities have been responsible for the deteriorating ambient air quality (Liu et al 2018;Tonne 2017;Jain 2017;Jain et al 2016;Kumar et al 2013). In the last two decades, the air pollution level in Delhi has augmented drastically, leading to increased morbidity in the form of chronic respiratory diseases, acute cardiovascular events, reproductive and developmental damage, allergies, and cancers, as well to a higher mortality rate (Jain et al 2021;Jain and Sharma, 2020;Biel et al 2020;Kumar and Mishra 2018;Landrigan et al 2017;Jain et al 2016;Aggarwal and Jain 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies concluded that exposure to BC is associated with cardiovascular effects [9,31,32]. Although the evidence linking BC to subclinical cardiovascular endpoints is more limited than that for PM 2.5 , BC is of interest from a health perspective because multiple studies report associations between combustion-related air pollution and health effects [31,[33][34][35].…”
Section: Introductionmentioning
confidence: 99%